Implementasi Manajemen Mutu Pendidikan dalam Meningkatkan Kinerja Guru di SD Negeri 172 Palembang - Niken, Niken; Aziz, Khoirul; Yulistiani, Windy; Afriantoni (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the implementation of educational quality management in improving teacher performance at SD Negeri 172 Palembang. The research method used is a qualitative approach with a field research design. Data collection techniques were carried out through interviews, observations, and documentation, involving the principal and teachers as informants. The data analysis technique begins with data collection, data presentation, verification, and conclusion drawing. The results show that the implementation of educational quality management at SD Negeri 172 Palembang has been carried out through systematic stages of planning, implementation, and evaluation. The application of quality management is also supported by a quality culture, academic supervision, and well-organized administrative systems. Teacher performance is categorized as fairly good, as indicated by the ability to plan, implement, and evaluate learning processes. However, there are still several obstacles such as limited facilities and suboptimal use of technology. The implementation of educational quality management has proven to have a positive impact on improving teacher performance, particularly in terms of professionalism, discipline, and learning quality. The limitation of this study lies in its scope, as it was conducted in only one school, so the results cannot yet be widely generalized. The recommendation is that the school should strengthen continuous evaluation, teacher training, and collaboration among school members so that the implementation of quality management becomes more effective in improving teacher performance.